(untitled) (Al-Mansour Journal, 2023)
Brick production in Iraq is considered among the first modern industries and the most developed, and of a strongest affect in the international economy. Planning for this industry in a crucial matter since brick is one of the main materials that its availability highly affects carrying out constructive and economic projects. Therefore, studies have been prepared for the future of this industry in order to promote, develop and expand it. The aim of this paper is to prohibit the amounts of Iraqi produced brick for the future period ( 2010 – 2019 ) by using the best suitable Box Jencks models (B-J). This paper has arrived at a number of conclusions: the best used model is ARIMA (0,1,2), we also found that the lowest levels of prohibition might be negative, this refers that it is in a case of great need for this material. The local production might not be enough; therefore, the country will be obliged to import the needed amount from abroad, taking into consideration that most brick factories in Iraq do not have the modern technologies and follow old methods in its industries which lead to slow and little amount of production. We recommend using the model arrived at in Box Jencks (B-J) method in order to make use of it in planning and prohibiting for future times. We also recommend the dependence on the prohibiting values derived from applying the model in designing the future plans. The country now is in great need for a vast reconstruction process; therefore, we recommend the increase of brick production and to expand the number of new modern factories to produce this important material